Knowledge transfer through internship: The EASLIS experience in strengthening the governance decentralisation programme in Uganda - Magara, Elisam; Bukirwa, Joyce; Kayiki, Robert (African Journal of Library, Archives & Information Science, 2011)
Makerere University, Kampala,Uganda has attempted over many years to integrate knowledge transfer programmes into its higher education programmes through various strategies, including internship and fieldwork studies. The internship programmes have gained popularity, especially through the interventions from the Innovations at Makerere Committee of the University that supported a number of academic units to enhance the decentralisation of the internship to the local governments in Uganda. The East African School of Library and Information Science (EASLIS) has implemented knowledge transfer of information management practices through its internship programme since 2006. This paper highlights the activities undertaken by EASLIS students during the internship and the perceptions of the field supervisors on the performance of students in terms of the students’ competences and performances, benefits to local governments, challenges being faced, and aspects requiring improvement. This internship programme has brought about significant changes, including improved perceptions in the community about the library and information science profession, the balancing of theory with practice in the delivery of EASLIS programmes, and improved professional confidence and abilities of its students and graduates. The paper is concluded with various recommendations addressed to the University and local governments for improving the benefits of the programme.